Determinants of Undernutrition among Adult Tuberculosis Patients Receiving Treatment in Public Health Institutions in Shashemane Town, Southern Ethiopia - Adane Tesfaye Anbese; Gudina Egeta; Frehiwot Mesfin; Abinet Arega Sadore (Journal of Nutrition and Metabolism)
Background. Undernutrition and tuberculosis are the major concerns of underdeveloped regions of the world. Tuberculosis makes undernutrition worse and undernutrition weakens immunity, thereby increasing the likelihood that latent tuberculosis will develop into active disease. Nevertheless, little has been understood about undernutrition among patients with infectious disease like tuberculosis in Ethiopia. This study was conducted to determine the magnitude of undernutrition and its determinants among tuberculosis patients in Shashemane public health institutions, Southern Ethiopia. Methods. An institution-based cross-sectional study was conducted in two public hospitals and ten health centers of Shashemane Town from March 12, to April 12, 2017, among 368 adult tuberculosis patients on treatment follow-up. Sociodemographic and socioeconomic characteristics and anthropometric data were collected. Data were entered into EpiData version 3.3 computer software and analyzed using SPSS version 20. Bivariable logistic regression analyses were done to assess the association between outcome variable at bivariate analysis, and multivariable logistic regression model was used to assess factors that were independently associated with undernutrition. Odds ratios along with 95% confidence interval (CI) were estimated to measure the strength of the association, and level of statistical significance was declared at P value ≤0.05. Result. The overall magnitude of undernutrition among adult tuberculosis patients in this study was 28.8% (95% CI = 0.25–0.34). Patients in the age group of forty-five and above ((AOR = 3.39, 95% CI = (1.6–7.18)), residents in rural area ((AOR = 1.95, 95% CI = (1.07–3.54)), those with problem with eating ((AOR = 2.361, 95% CI = (1.332–4.185)), and those who are not on food supplementation ((AOR = 2.21, 95% CI = (1.06–4.58)) were significantly at higher risk of undernutrition. Conclusion. The magnitude of undernutrition in the study setting was found to be significantly higher. Age greater than forty-five, living in rural area, and lack of nutritional care and support were identified as the factors associated with undernutrition. Thus, relevant actors should give attention to fast nutritional intervention together with standard therapeutic regimen in the management of pulmonary tuberculosis patients to curb their nutritional derangement.